Colonic J-Pouch or Straight Colorectal Reconstruction After Low Anterior Resection For Rectal Cancer: Impact on Quality of Life and Bowel Function. Issue 11 (November 2020) - Gavaruzzi, Teresa; Pace, Ugo; Giandomenico, Francesca; Pucciarelli, Salvatore; Bianco, Francesco; Selvaggi, Francesco; Restivo, Angelo; Asteria, Corrado Rosario; Morpurgo, Emilio; Cuicchi, Dajana; Jovine, Elio; Coletta, Diego; et al.
Abstract : BACKGROUND: Patient-reported outcomes associated with different bowel reconstruction techniques following anterior resection for rectal cancer are still a matter of debate. OBJECTIVE: This study aimed to assess quality of life and bowel function in patients who underwent colonic J-pouch or straight colorectal anastomosis reconstruction after low anterior resection. DESIGN: Bowel function and quality of life were assessed within a multicenter randomized trial. Questionnaires were administered before the surgery (baseline) and at 6, 12, and 24 months after surgery. SETTINGS: Patients were enrolled by 19 centers. The enrollment started in October 2009 and was stopped in February 2016. The study was registered at www.clinicaltrials.gov (Identifier: NCT01110798). PATIENTS: Patients who underwent low anterior resection for primary mid-low rectal cancer and who were randomly assigned in a 1:1 ratio to receive either stapled colonic J-pouch or straight colorectal anastomosis were selected. MAIN OUTCOME MEASURES: The primary outcomes measured were quality of life and bowel function. RESULTS: Of the 379 patients who were evaluable, 312 (82.3%) completed the baseline, 259 (68.3%) the 6-month, 242 (63.9%) the 12-month, and 199 (52.5%) the 24-month assessment. Bowel functioning and quality of life did not significantly differ between arms for almost all domains. The total bowel function score, the urgency, and the stool fractionation scores significantly worsened after surgery and remained impaired over time in both arms ( p < 0.0032), whereas constipation improved after surgery but recovered to baseline levels from 1 year onward ( p < 0.0036). All patients showed a significant and continuous improvement in emotional functioning ( p < 0.0013) and future perspective ( p < 0.0001) from baseline to the end of the study. LIMITATIONS: Limitations of the study include missing data, which increased over time; the possibility that some treatments have slightly changed since the study was conducted; and investigators not blind to treatment allocation. CONCLUSION: The findings of this study do not support the routine use of colonic J-pouch reconstruction in patients with rectal cancer who undergo a low anterior resection. See Video Abstract at http://links.lww.com/DCR/B328 . BOLSA J COLÓNICA O RECONSTRUCCIÓN COLORRECTAL RECTA DESPUÉS DE RESECCIÓN ANTERIOR BAJA PARA CÁNCER RECTAL: IMPACTO EN LA CALIDAD DE VIDA Y LA FUNCIÓN INTESTINAL: UN ESTUDIO ALEATORIZADO PROSPECTIVO MULTICÉNTRICO: ANTECEDENTES: Los resultados informados por el paciente asociados con diferentes técnicas de reconstrucción intestinal después de la resección anterior para el cáncer de recto aún son tema de debate. OBJETIVO: Evaluar la calidad de vida y la función intestinal en pacientes que se sometieron a una bolsa en J colónica o reconstrucción de anastomosis colorrectal recta después de una resección anterior baja. DISEÑO: La función intestinal y la calidad de vida se evaluaron en un ensayo aleatorizado multicéntrico. Los cuestionarios se administraron antes de la cirugía (basal) y a los 6, 12 y 24 meses después de la cirugía. MARCO: Los pacientes fueron incluidos en 19 centros. La inscripción comenzó en Octubre de 2009 y se detuvo en Febrero de 2016. El estudio se registró en www.clinicaltrials.gov (Identificador: NCT01110798). PACIENTES: Pacientes que se sometieron a resección anterior baja por cáncer rectal primario medio-bajo y que fueron aleatorizados en una proporción de 1: 1 para recibir bolsa J colónica con grapas o anastomosis colorrectal recta. MEDIDAS DE RESULTADOS PRINCIPALES: calidad de vida y función intestinal. RESULTADOS: De los 379 pacientes que fueron evaluables, 312 (82.3%) completaron la evaluación inicial, 259 (68.3%) a los 6 meses, 242 (63.9%) a los 12 meses y 199 (52.5%) a los 24 meses. . El funcionamiento intestinal y la calidad de vida no difirieron significativamente entre los dos grupos en casi todos los dominios. La puntuación total de la función intestinal, la urgencia y las puntuaciones de fraccionamiento de las heces empeoraron significativamente después de la cirugía y continuaron con el tiempo extra en ambos grupos ( p <0.0032), mientras que el estreñimiento mejoró después de la cirugía pero se recuperó a los niveles basales a partir de 1 año en adelante ( p <0.0036). Todos los pacientes mostraron una mejora significativa y continua en el funcionamiento emocional ( p <0.0013) y la perspectiva futura (<0.0001) desde el inicio hasta el final del estudio. LIMITACIONES: Datos faltantes, que aumentaron con el tiempo; la posibilidad de que algunos tratamientos hayan cambiado ligeramente desde que se realizó el estudio; investigadores no cegados a la asignación del tratamiento. CONCLUSIÓN: Los hallazgos de este estudio no respaldan el uso rutinario de la reconstrucción de la bolsa J colónica en pacientes con cáncer rectal que se someten a una resección anterior baja. Consulte Video Resumen en http://links.lww.com/DCR/B328 . (Traducción—Dr. Yesenia Rojas-Khalil ) Abstract : Supplemental Digital Content is available in the text.